Evaluation of the complications of the in situ versus uterine exteriorization repair of caesarean section uterine incision - Abdelfattah, Eman Aly; Elfazary, Hisham Adel; Galal, Hisham Mostafa; Elgyar, Salwa Mostafa Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: caesarean section is the most performed major operation around the world. In this study we aim to compare in situ repair of caesarean section uterine incision to repair with uterine exteriorization. Methods: The study was conducted on 200 patients at El-Shatby maternity university hospital during the period from June 2019 to June 2020 and after ethical committee approval and obtaining an informed consent. All cases were 37 weeks gestation or more with singleton fetus prepared to have caesarean section. They were randomly allocated into 2 groups each of 100 participants: group A: with exteriorization repair of the uterus, group B: with in situ repair. After history taking, examination and laboratory investigations, elective caesarean section was done under spinal anesthesia. After delivery of the fetus and placenta, the uterus was repaired either in situ or after exteriorization followed by closure of the abdomen in layers. We assessed: primary outcome: blood loss. secondary outcome: nausea or vomiting, hypotension, operative time and duration of uterine repair, tachycardia, uterine contractility and hematoma formation. Post-operative pain, febrile illness, time of ambulation, time of return of bowel function were also assessed. Data were collected and submitted to statistical analysis. Results: In situ repair had a statistically significant decrease in intra operative nausea, vomiting and tachycardia. Exteriorization resulted in significantly shorter duration of uterine repair; unlikely duration of the whole surgery was not statistically significant. Return of intestinal sounds was statistically significant in favour of in situ repair. Conclusions: There is no definite or absolute privilege of in-situ repair versus exteriorization.